Phytosanitary quality of Brachiaria brizantha 'BRS Piata' seeds in function of climate conditions - Silva, Givanildo Z. da; Martins, Cibele C. [UNESP]; Nascimento, Luciana C. do; Barreto, Gabriel G.; Farias, Otilia R. de (Univ Federal Campina Grande, 2019)
Infected seeds are one of the main pathogen transmission vehicles, and they are responsible for significant losses in production fields; phytosanitary defense depends on the inoculum and climatic factors. Thus, in this study, it was aimed to identify climatic variables of the regions that propitiate the production of Brachiaria brizantha 'BRS Piata' seeds infected with phytopathogenic fungi. Temperature and rainfall data were obtained from 10 production fields, and phytosanitary quality of the seeds was evaluated with the filter paper method; the means were compared using the Kruskal-Wallis non-parametric analysis. Principal component analysis was performed to determine the relationship between the climatic variables and seed phytosanitary quality. Sites with maximum temperatures higher than 30 degrees C, mean values close to 25 degrees C, and rainfall less than 82 mm during harvest were favorable to the incidence of Fusarium spp. The incidence of Bipolaris sp. in the seeds of Piata grass was favored by temperatures around 19 and 20 degrees C during the maturation phase. The highest incidence of Exserohilum sp. occurred at the sites in which the temperature during harvest was close to 20 degrees C and accumulated rainfall, between 167 and 181 mm.
Keywords: forage grasses; Piata grass; temperature; humidity; phytosanitary barrier